2004
DOI: 10.7589/0090-3558-40.3.501
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and Persistent Organic Pollutant Concentrations in African Fish Eagles, Marabou Storks, and Nile Tilapia in Uganda

Abstract: The purpose of this research was to evaluate persistent organic pollutant (POP) and mercury concentrations in tissues of African fish eagles (Haliaeetus vocifer) and Nile tilapia (Oreochromis niloticus) from Lake Victoria near Entebbe and Lake Mburo, Uganda. Marabou stork (Leptoptilos crumeniferus) nestlings from urban Kampala (40 km from Entebbe) also were sampled for POPs and mercury. Total mercury was measured in the breast feathers of eight nestling and 10 adult African fish eagles from Lake Mburo, 10 nest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Surprisingly, the concentration of DDE found in this study is similar to that detected in wild Nile tilapia from Lake Victoria sampled in Entebbe Market, Uganda, where 63% of the samples (n ¼ 8) were found to contain 4,4 0 -DDE with a mean concentration of 0.002 AE 0.001 mg kg À1 (wet weight) (Hollamby et al 2003). The concentration and prevalence of organochlrorine pesticides determined by the study are, however, different from those reported by a more recent study using a larger sample of Nile tilapia from Lake Victoria in Uganda, where the BHC level of 0.74 ng g À1 , aldrin (0.28 ng g À1 ), endosulfan (1.70 ng g À1 ), dieldrin (0.30 ng g À1 ), DDE (0.80 ng g À1 ), and DDT (0.59 ng g À1 ) were detected (Kasozi et al 2006).…”
Section: Levels Of Organochlorine Pesticides and Polychlorinated Biphsupporting
confidence: 77%
See 2 more Smart Citations
“…Surprisingly, the concentration of DDE found in this study is similar to that detected in wild Nile tilapia from Lake Victoria sampled in Entebbe Market, Uganda, where 63% of the samples (n ¼ 8) were found to contain 4,4 0 -DDE with a mean concentration of 0.002 AE 0.001 mg kg À1 (wet weight) (Hollamby et al 2003). The concentration and prevalence of organochlrorine pesticides determined by the study are, however, different from those reported by a more recent study using a larger sample of Nile tilapia from Lake Victoria in Uganda, where the BHC level of 0.74 ng g À1 , aldrin (0.28 ng g À1 ), endosulfan (1.70 ng g À1 ), dieldrin (0.30 ng g À1 ), DDE (0.80 ng g À1 ), and DDT (0.59 ng g À1 ) were detected (Kasozi et al 2006).…”
Section: Levels Of Organochlorine Pesticides and Polychlorinated Biphsupporting
confidence: 77%
“…Using the same approach, the wet weight concentrations for the maximum concentration obtained for Hg in African catfish and Nile tilapia (Table 2) were determined as 0.06 and 0.074 mg kg À1 , respectively, which were also below the USFDA action levels and European Union's MRLs. The Hg levels obtained for farmed Nile tilapia appear to be higher than those reported earlier at 0.01 mg kg À1 (wet weight) for wild fish from Lake Victoria and Lake Mburo in Uganda (Hollamby et al 2003). These residue levels are also higher than those obtained in muscles of several fish species in Japan (Yamashita et al 2005), suggesting that farm-raised fish accumulate more Hg than wild fish.…”
Section: Heavy Metal Residuesmentioning
confidence: 52%
See 1 more Smart Citation
“…Feathers are an excellent, non-invasive tissue to sample for chemicals that are largely endogenously derived, such as mercury (Burger, 1993;Hollamby et al, 2004d). Feather mercury concentrations can vary depending on the order the sampled feather has in the sequence of the molt cycle with body contour feathers showing the least variation in mercury content (Furness et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic at the class level is birds molt their feathers and this uniquely avian tissue is useful as an indicator of whole body concentrations of certain heavy metals (Burger, 1993). A characteristic at the genus level is the predominantly piscivorous diet of many Haliaeetus genus eagles that allows for the determination of the origin of tissue concentrations of pollutants (Helander et al, 1982;Bowerman et al, 2003;Hollamby et al, 2004d). As well as biological, physiological, behavioural and reproductive characteristics of the biomonitor species, knowledge of ecological structure and function, and form and cycling of the chemical (or change) within the environment being examined, is required (Douthwaite, 1992;Jefree et al, 2001).…”
Section: Introductionmentioning
confidence: 98%